2019
DOI: 10.1097/ogx.0000000000000655
|View full text |Cite
|
Sign up to set email alerts
|

“Pregnancy Brain”: A Review of Cognitive Changes in Pregnancy and Postpartum

Abstract: Importance The idea that pregnant women suffer from deficits in memory is widespread but poorly documented in obstetrical literature. Objective To review available psychology literature on the subject of cognitive changes in pregnancy in order to guide the prenatal care provider on how to counsel pregnant women. Evidence Acquisition An extensive review of PubMed and PsycINFO databases was conducted to gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 54 publications
6
22
0
Order By: Relevance
“…Consistent with the anecdotal and self-report literature 8,9,13,15,27,28 , we hypothesised that mothers would self-report worse subjective memory than non-mothers but out-perform non-mothers in objective tests of cognitive performance.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Consistent with the anecdotal and self-report literature 8,9,13,15,27,28 , we hypothesised that mothers would self-report worse subjective memory than non-mothers but out-perform non-mothers in objective tests of cognitive performance.…”
supporting
confidence: 68%
“…The copyright holder for this preprint this version posted June 7, 2021. ; https://doi.org/10.1101/2021.06.07.447303 doi: bioRxiv preprint of cognitive difficulties related to pregnancy and parenthood that do not necessarily resolve upon the birth of the child 8,9,13,15,27,28 . Indirect evidence from neuroimaging studies suggests that the maternal brain undergoes dynamic plastic changes during pregnancy and the postpartum period which may be indicative of cognitive changes.…”
mentioning
confidence: 99%
“…A recently published review of cognitive changes in pregnancy and postpartum that analyzed a substantial number of studies in animals and humans, found that there is little agreement on the type and the degree of memory impairment 37 . Cognitive performance seems to be diminished rather than enhanced in humans, whereas animal research overwhelmingly supports enhanced memory function during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus plays a central role in the processing of emotional and cognitive behaviors (Korotkova et al, 2018). Unlike general major depression disorder and cognitive impairment, with pathogenic mechanisms associated with psychosocial stress or neurological injury, postpartum symptoms are often speculated to be caused by hormonal fluctuations (Becker et al, 2016;Brown and Schaffir, 2019). A growing number of studies have shown that hippocampus-related mechanisms are implicated in the pathogenesis of postpartum emotional and cognitive dysfunction (Pawluski and Galea, 2007;Baka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%